Challenges and Facilitating Factors in Accessing Administrative Data for Research: Insights from the Children's Health Profile and Trajectory Initiative in NB and PEI. (2018) - Sparks, Sarah; Tranchant, Carole; Malinski, Patricia; Montelpare, William; Bélanger, Mathieu; Miedema, Baukje; Bouchard, Danielle; Sénéchal, Martin; Jose, Caroline; Barre, Ed; Rossiter, Misty; Bryanton, Janet; et al.
No abstract available